2011
DOI: 10.3136/fstr.17.369
|View full text |Cite
|
Sign up to set email alerts
|

Baking Properties of Saccharomyces cerevisiae Strains Derived from Brem, a Traditional Rice Wine from Bali

Abstract: Twenty-two strains of Saccharomyces cerevisiae isolated from tape-mash for the production of brem, a traditional rice wine from Bali, Indonesia, were divided into three groups (I, II, and III) based on the sequences of the rDNA spacer region and SUC2 gene. DNA analyses suggested that the seventeen strains in groups II and III were taxonomically closer to baking strains than the five strains in group I. These differences were reflected in their leavening ability in dough with and without addition of 5% sucrose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Ragi tapai is a dry starter culture made from rice flour, spices, and water or sugarcane juice/extract [9,10]. Various amylolytic and fermentative microbes have been isolated from various brands of ragi tapai acquired from various places and markets, such as Amylomyces rouxii, Rhizopus oryzae, Endomycopsis burtonii, Mucor sp., Candida utilis, Saccharomycopsis fibuligera, Saccharomyces cerevisiae and some lactic acid bacteria Pediococcus pentosaceus, Lactobacillus plantarum, and L. fermentum [10][11][12]. Studies from the Philippines, Malaysia, Thailand, and Vietnam found similar microbial species in the inoculum of tapai [10].…”
Section: Introductionmentioning
confidence: 95%
“…Ragi tapai is a dry starter culture made from rice flour, spices, and water or sugarcane juice/extract [9,10]. Various amylolytic and fermentative microbes have been isolated from various brands of ragi tapai acquired from various places and markets, such as Amylomyces rouxii, Rhizopus oryzae, Endomycopsis burtonii, Mucor sp., Candida utilis, Saccharomycopsis fibuligera, Saccharomyces cerevisiae and some lactic acid bacteria Pediococcus pentosaceus, Lactobacillus plantarum, and L. fermentum [10][11][12]. Studies from the Philippines, Malaysia, Thailand, and Vietnam found similar microbial species in the inoculum of tapai [10].…”
Section: Introductionmentioning
confidence: 95%
“…Baker’s yeast plays an important role in fermentation for the expansion of bread dough; the production of CO 2 , organic acids and esters by yeast improves dough texture. The identification and characterization of numerous yeast strains [ 1 ] have indicated Saccharomyces cerevisiae as the main species used in industrial bread production. The primary ingredient of dough is starch, which is hydrolyzed to maltose by the activity of enzymes such as amylase.…”
Section: Introductionmentioning
confidence: 99%